Relative growth and population dynamics of Macrobrachium iheringi (decapoda, palaemonidae) - Nogueira, Caio dos Santos [UNESP]; Perroca, Júlia Fernandes [UNESP]; Piantkoski, Emerson Luiz [UNESP]; da Costa, Rogerio Caetano [UNESP]; Taddei, Fabiano Gazzi; Fransozo, Adilson [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
During the ontogenetic development of crustaceans, the relative growth of some structures may change, especially during the transition from juvenile to adult. This study describes the relative growth of body structures of Macrobrachium iheringi, and provides information on its population dynamics, such as structure, fecundity, and morphological sexual maturity. The sampling of M. iheringi was carried out in “Ribeirão da Hortelã, in Botucatu (SP, Brazil). The length of the carapace (CL), abdomen (AL), and ischium (IL), merus (ML), carpus (CrL), propodus (PpL), and dactyl (DcL) of the second right pereopod were measured. In addition, the width of the second abdominal pleura (PW) and propodus height (PpH) were included in analyses. The relationships that best demonstrated the changes in the allometric coefficient were CL vs PpL in males and females. The CL, in which males and females reach morphological sexual maturity, was estimated as 13.3 mm and 11.1 mm, respectively. The sex-ratio differed from the expected 1:1 and was skewed towards females. Precipitation and temperature influenced the abundance of different demographic classes. Macrobrachium iheringi has few but large eggs, which is expected since this species has an abbreviated larval development. Based on these results, we conclude that the propodus are good indicators of the size at onset of morphological sexual maturity. In addition, important information was obtained on the biology of M. iheringi, including its life cycle pattern, reproduction and influence of abiotic factors.
Keywords: Allometry; Caridea; Freshwater; Populations; Sex-ratio